Rightward and leftward head rotation influence the geometric features of the healthy carotid bifurcation - Brott, Brigitta C.; Aristokleous, Nicolas; Seimenis, Ioannis; Papaharilaou, Yannis; Georgiou, Georgios C.; Anayiotos, Andreas (My University, 2011)
Posture changes may influence the geometry and hemodynamics of the carotid bifurcation [1]. As a result, head rotation may cause geometric changes that alter the hemodynamic variables previously cited to correlate with the development of atherosclerosis. Such variables include oscillating wall shear stress (WSS) and particle residence times. Glor et al. [1] had reported changes in the right carotid bifurcation geometry with leftward rotation of the head. We have previously reported that geometric differences in the right and left carotid bifurcation occur with a rightward rotation of the head [2]. To investigate the geometric changes in the carotid geometry that occur in the prone sleeping position with rightward and leftward head rotation, we have performed studies in two healthy young volunteers. We defined specific geometric parameters of the carotid bifurcation, such as bifurcation angle, internal carotid artery (ICA) angle, ICA planarity angle, in-plane asymmetry angle, tortuosity, curvature, area and diameter ratios, and compared their corresponding values in three head postures: 1) the supine neutral position, 2) the prone sleeping position with head rotation to the right (∼80 degrees), and 3) the prone sleeping position with head rotation to the left (∼80 degrees).
Keywords: Carotid bifurcation; Hemodynamic; Wall shear stress; Carotid geometry